The Congo Curse: From Heart of Darkness through King Leopold’s Ghost, King Leopold’s Soliloquy to In the Footsteps of Mr. Kurtz: Living on the Brink of Disaster in Mobutu’s Congo - Warfa, Ahmed Osman; Mwetu, Lester (International Journal of Culture and History, 2023)
This article explores the intricacies that have shaped the political and economic landscape of Congo from colonial period to post-independence times. The examination of the situation in Congo is undertaken though the eyes of Joseph Conrad in Heart of Darkness (1899), Mark Twain in King Leopold’s Soliloquy (1905), Adam Hochschild in King Leopold’ Ghost (1998) and Michela Wrong in In the Footsteps of Mr. Kurtz: Living on the Brink of Disaster in Mobutu’s Congo (2000). In his novella, Conrad navigates through the Congo River and penetrates into the interior of Congo and ushers us to the emergence of European imperial powers in Africa. In this compelling tale, Conrad explores the European’s exploration and exploitation of the Congo under Belgium’s King Leopold II. In King Leopold’s Soliloquy Mark Twain largely satirizes King Leopold’s self-importance while plundering Congo while Hochschild in King Leopold’ Ghost advances King Leopold’s state capture of Congo Free State and making the country his own property. Michela Wrong’s In the Footsteps of Mr. Kurtz captures Congo’s tribulation under Mobutu’s regime. Wrong navigates the political journey of post-independence Congo and seems to suggest that the Congolese people are not free from political and economic sabotage from leaders who have personalized the country even after the exit of the white man. This paper therefore examines the personalities of King Leopold II of Belgium and Joseph Desire Mobutu of the independent Congo as projected in the selected texts. The article shows that the Congo curse is deeply rooted in the country’s political leadership and examines the insatiable appetite of King Leopold II and Joseph Desire Mobutu for the mineral wealth through the lenses of the four selected texts.